Siklus hidup dan statistik demografi kutukebul Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) biotipe B dan non-B pada tanaman cabai (Capsicum annuum L.) - Purnama Hidayat; Hazen Arrazie Kurniawan; Lutfi Afifah; Hermanu Triwidodo (Perhimpunan Entomologi Indonesia, 2017)
The whitefly Bemisia tabaci (Gennadius) biotype B also known as Bemisia argentifolii (Gennadius) is a more malignant whitefly biotype in damaging plants compared to non-B biotype. Currently the whitefly B. tabaci biotype B has been reported to exist in Indonesia. Basic information such as life cycle, length of life, fecundity, and breeding ability of a whitefly is important information as a basis in preparing the whitefly control strategy. The aim of this research was to study the life cycle and demographic statistic of the B. tabaci biotype B and the non-B biotype on chili pepper. The study was conducted by observing the development of the whiteflies from eggs to adult in a growth chamber that the temperature and lighting were controlled. Observations were made on several aspects of biology and some parameters of demographic statistics. The results showed that the biotype B of B. tabaci has several different biological aspects with the non-B whitefly in chili pepper. The life cycle of the biotype B of B. tabaci and the non-B were different, 33.27 and 30.86 days respectively. The biotype B of B. tabaci had a net reproduction rate (R0) which was similar to that of the non-B biotype as well as the average of its generation. However, the intrinsic increase rate (r) of the biotype B B. tabaci was 2.5 times shorter than the non-B biotype. The biotype B of B. tabaci doubled its population (DT) 2 times faster than the non-B biotype. It is clear that the biotype B of B. tabaci potentially more dangerous than the non-B.